LGBT and Pancasila, Between the Essence of Human Rights Protection and the Existence of Pancasila Values and Islamic Law - Majid, Nurchaliq (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Speaking of rights, of course we are talking about rights which are fundamentally inherent in human beings. Be it the right of life, the right of welfare, the right to justice, and the right of social security as embodied in the 1945 constitution. LGBT communities want the same thing, get the same rights, with principles of freedom and principles of equality. Not only does the LGBT community want legal protection against its freedom but also the legality of its existence in Indonesia. This article aims to learn the essence of human rights protection against LGBT (lesbian, gay, bisexual, and transgender) and its conversion to the existence of pancasila values and Islamic law, which is intended to find common points in both, is qualitative in the use of literature study methods (library research). As for the results of this study, LGBT basically has a right to cure abuses, not the claims of freedom to campaign, and to preserve existence in Indonesia. Certainly, one of its restriction reviews or ladsments is a consideration of religious morality that has always held a high regard for human dignity and dignity. There is also a value to maintain, there is a value embodied in the pancasila that gives the message, that every citizen must maintain a value and be irreparable.